A preparation method of 4D printable shape memory polyimide composite aerogel material

By using polyamic acid ink of composite carboxylated carbon nanotubes, combined with DIW technology and freezing assisted molding, the problem of poor shape memory performance of polyimide aerogel is solved, and a higher recovery rate and volume stability is achieved, which improves its application capabilities in the field of 4D printing.

CN116554539BActive Publication Date: 2025-04-25JIANGNAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310241930.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-13
Publication Date
2025-04-25
Estimated Expiration
2043-03-13

AI Technical Summary

Technical Problem

Polyimide aerogel has poor shape memory performance, especially poor recovery rate and large volume shrinkage, which limits its application in the field of 4D printing.

Method used

Polyamic acid of composite carboxylated carbon nanotubes is used as ink, and through DIW technology and freezing assisted molding, a polyimide aerogel enhanced by carboxylated carbon nanotubes with specific structures is constructed, which weakens volume shrinkage and improves mechanical and thermal conductivity.

Benefits of technology

The shape memory performance of polyimide aerogels is significantly improved, including the recovery rate and shape fixation rate, improved volume stability and thermally induced shape memory performance, and enhanced its application potential in 4D printing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116554539B_ABST
    Figure CN116554539B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a 4D printable shape memory polyimide composite aerogel material, and belongs to the technical field of aerogel material preparation. The preparation of the 4D printable shape memory polyimide composite aerogel material of the present invention uses polyamic acid of composite carboxylated carbon nanotubes as ink, and can accurately and effectively construct a shape memory polyimide composite aerogel material with a specific structure and excellent 4D printable performance by DIW technology with the aid of freezing-assisted molding. At the same time, it also solves the problems of poor formability and large volume shrinkage of existing polyimide aerogels. The preparation process is simple, the cost is low, and the controllability is good. It is a green preparation method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a 4D printable shape memory polyimide composite aerogel material, belonging to the technical field of aerogel material preparation. Background Art

[0002] 4D printing, as a new material molding method, refers to the introduction of time as an additional dimension based on 3D printing, which helps to change the function or shape of 3D printed products in a controllable way. 4D printing is a revolutionary technology that can automatically and quickly fold into the corresponding shape according to the product design without a printer, and has extremely high requirements for the flexibility and resilience of the material.

[0003] The shape memory effect refers to the ability of a material to select and control the material system to return from a temporary state to its original state in a preset manner under external stimulation. Shape memory polymers can return to their original state when subjected to external stimulation, and this property has established their important position in the field of 4D printing technology.

[0004] Polyimide aerogel materials have been widely studied due to their advantages such as high mechanical strength, high modulus and excellent thermal stability. At present, the molding methods of polyimide aerogels are mainly limited to casting and molding, and the aerogel products prepared have a single structure; and the polyimide aerogels prepared by freeze-drying usually undergo significant volume shrinkage, which greatly affects the dimensional stability of the sample and has poor shape memory performance. The use of 3D printing technology to prepare polyimide aerogels can enrich its molding methods and expand its structural design; but 3D printing has high requirements on ink performance, and usually exhibits fluid properties with a loss modulus greater than the storage modulus under low shear stress. The printing ink cannot effectively maintain the 3D printed structure after being extruded by the needle and collapses; especially when it is prepared into 4D printable materials by 3D printing, its application is greatly limited. Summary of the invention

[0005] The purpose of the present invention is to improve the poor shape memory performance of polyimide composite aerogel, especially the poor recovery rate and other shortcomings; at the same time, to improve the disadvantages of the large volume shrinkage rate of polyimide aerogel, and further improve the 4D printable shape memory performance of polyimide aerogel.

[0006] The present invention provides a method for preparing a 4D printable shape memory polyimide composite aerogel material, wherein the method uses polyamic acid composited with carboxylated carbon nanotubes as ink, and can accurately and effectively construct a carboxylated carbon nanotube-reinforced polyimide aerogel with a specific structure by DIW technology with the aid of freeze-assisted molding; wherein the use of carboxylated carbon nanotubes as a reinforcing agent can effectively reduce the volume shrinkage of the aerogel and improve the mechanical properties of the polyimide aerogel. At the same time, carboxylated carbon nanotubes, as a filler with excellent thermal conductivity, can also improve the thermal conductivity of the polyimide aerogel to a certain extent, thereby improving the thermal shape memory performance of the polyimide aerogel, that is, it has excellent 4D printable performance.

[0007] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0008] The first object of the present invention is to provide a method for preparing a 4D printable shape memory polyimide composite aerogel material, the method comprising the following steps:

[0009] (1) adding carboxylated carbon nanotubes into water and dispersing them uniformly to form a carboxylated carbon nanotube dispersion; then adding polyamic acid dry silk and triethylamine into the carboxylated carbon nanotube dispersion, heating and stirring to disperse them uniformly, and obtaining a composite ink;

[0010] (2) loading the composite ink prepared in step (1) into a 3D printer for 3D printing and freeze-molding; placing the molded material in a freeze dryer for freeze drying, and then performing a thermal imidization treatment to obtain a 4D printable shape memory polyimide composite aerogel having a three-dimensional grid structure.

[0011] In one embodiment, the length of the carboxylated carbon nanotubes in step (1) is 30 nm to 50 nm; and the polyamic acid is polyamide dry filaments.

[0012] In one embodiment, the mass ratio of the carboxylated carbon nanotubes, polyamic acid and triethylamine in step (1) is 0.75-3:9:4.5; preferably 0.75-1.5:9:4.5.

[0013] In one embodiment, the heating and stirring in step (1) is at 40-60° C. and the stirring is for 6-12 hours.

[0014] In one embodiment, the mass percentage of polyamic acid in the composite ink of step (1) is 6-10%, preferably 7.7%-7.9%.

[0015] In one embodiment, the solid content of the composite ink in step (1) is 7%-12%.

[0016] In one embodiment, the preparation of the polyamic acid in step (1) includes the following steps: firstly dissolving a polymerizable diamine monomer in a polar solvent, then adding a dibasic anhydride monomer, and carrying out a polymerization reaction in an ice-water bath for 3-6 hours, then adding a co-solvent triethylamine, and continuing the reaction for 2-5 hours to obtain a polyamic acid solution; placing the obtained polyamic acid solution at a height of 0.5 m to 1 m, slowly flowing it into ultrapure ice water, precipitating to obtain filamentous polyamic acid, and then freeze-drying the filamentous polyamic acid to obtain polyamic acid dry filaments.

[0017] In one embodiment, the polymerizable monomer diamine includes 4,4'-diaminodiphenyl ether or p-phenylenediamine; the dianhydride monomer includes one or more of pyromellitic dianhydride, diphenyl ether tetracarboxylic dianhydride, 4,4'-biphenyl ether dianhydride, 3,3',4,4'-dibenzophenone tetracarboxylic dianhydride or biphenyl tetracarboxylic dianhydride.

[0018] In one embodiment, the polar solvent includes one or more of N,N-dimethylacetamide, N-methylpyrrolidone or dimethylformamide.

[0019] In one embodiment, the 3D printing in step (2) is specifically as follows: the composite ink is transferred into a syringe, and after debubbling by a high-speed centrifuge, it is printed by a 3D printer; wherein the needle diameter of the syringe is 0.1 mm to 2 mm; the debubbling time is 5 min to 15 min; and the 3D printing speed is 4 mm s -1 ~10mm s -1 , the printing air pressure is 0.05MPa~0.3MPa.

[0020] In one embodiment, the 3D printed structure includes a grid structure, a honeycomb structure, a three-dimensional frame structure, a cubic structure, a hollow frame structure or a pyramid structure.

[0021] In one embodiment, the freeze molding in step (2) is performed in a low temperature constant temperature reaction bath, and the low temperature is -5°C to 0°C.

[0022] In one embodiment, the temperature of the freeze dryer in step (2) is -20°C to -50°C, and the time is 72h to 96h.

[0023] In one embodiment, the temperature of the thermal imidization in step (2) is 200-350° C., and the time is 1-3 hours.

[0024] The second object of the present invention is to provide a 4D printable shape memory polyimide composite aerogel material prepared by the above method.

[0025] The third object of the present invention is to provide an application of the above-mentioned 4D printable shape memory polyimide composite aerogel material in the preparation of automobiles, intelligent robots, aerospace vehicles, and intelligent wearable devices.

[0026] A fourth object of the present invention is to provide a method for improving the recovery rate of shape memory polyimide composite aerogel, the method comprising the following steps:

[0027] (1) adding carboxylated carbon nanotubes into water and dispersing them uniformly to form a carboxylated carbon nanotube dispersion; then adding polyamic acid dry silk and triethylamine into the carboxylated carbon nanotube dispersion, heating and stirring to disperse them uniformly, and obtaining a composite ink;

[0028] (2) loading the composite ink prepared in step (1) into a 3D printer for 3D printing and freeze molding; placing the molded material in a freeze dryer for freeze drying and thermal imidization to obtain a 4D printable shape memory polyimide composite aerogel having a three-dimensional grid structure.

[0029] Beneficial effects of the present invention:

[0030] The preparation process of the present invention is simple, environmentally friendly, and easy to operate. It is a green chemical preparation method. By using carboxylated carbon nanotubes as a reinforcing agent, the volume shrinkage of the aerogel can be effectively improved, and because the carboxylated carbon nanotubes will be oriented along the extrusion direction of the needle under the shear force of the needle, it plays a role of physical reinforcement, so it can improve the mechanical properties of the polyimide aerogel. And with the help of freezing-assisted molding, it is ensured that the composite ink can maintain the structure of 3D printing well and will not collapse after extrusion. At the same time, carbon nanotubes, as a filler with excellent thermal conductivity, can also improve the thermal conductivity of aerogel to a certain extent, thereby improving the thermal shape memory performance of aerogel, especially the recovery rate of aerogel. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is an optical picture of the "butterfly" shaped carboxylated carbon nanotube-reinforced polyimide aerogel prepared in Example 2 of the present invention;

[0032] Figure 2 This is a SEM electron microscope image of the grid-structured carboxylated carbon nanotube-reinforced polyimide aerogel prepared in Example 2 of the present invention; wherein (a) is the top surface morphology of the aerogel, and (b) is the internal morphology of the polyimide aerogel;

[0033] Figure 3 The shape fixation rate and shape recovery rate data graph of the carboxylated carbon nanotube-reinforced polyimide aerogel prepared in Examples 1-4 of the present invention and Comparative Example 1;

[0034] Figure 4 This is a data graph of shape recovery rate of carboxylated carbon nanotube-reinforced polyimide aerogel prepared in Examples 1-4 of the present invention and Comparative Example 1;

[0035] Figure 5 The shape fixation rate and shape recovery rate data graph of the polyimide composite aerogel prepared in Example 2 of the present invention and Comparative Example 2;

[0036] Figure 6 This is a data graph of shape recovery rate of the polyimide composite aerogel prepared in Example 2 of the present invention and Comparative Example 2;

[0037] Figure 7 Optical images of the inks prepared in Example 1 and Comparative Example 3 of the present invention;

[0038] Figure 8 The graphs are data of rheological properties test of inks prepared in Examples 1-4 of the present invention and Comparative Example 1; wherein (a) is a modulus-shear strain relationship curve, and (b) is an apparent viscosity-shear rate relationship curve;

[0039] Fig. 9 This is an optical image of the carboxylated carbon nanotube-reinforced polyimide aerogel prepared in Comparative Example 4. DETAILED DESCRIPTION

[0040] The present invention is further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the appended claims of the present application. All raw materials are purchased from Sinopharm Chemical Reagent Co., Ltd., and the purity is chemically pure or analytically pure unless otherwise specified.

[0041] The method for determining the shape memory properties of the polyimide aerogel involved in the present invention is as follows:

[0042] The prepared ink was used to print a sample with a certain curvature for tensile shape memory performance testing. The sample was tested at a frequency of 1 Hz using a dynamic thermal mechanical properties tester (DMA Q800, TA Company, USA) in the controlled strain mode. The detailed test program design is as follows:

[0043] (1) Clamp the sample and set the force to 0.001 N; heat to 300 °C at a heating rate of 5 °C / min; keep warm for 10 min; apply strain to 15% (ε Total); cool down to 50°C at a cooling rate of 5°C / min; unload stress to 0.001Mpa at a stress unloading rate of 5Mpa / min; keep warm for 5min to obtain the shape fixed strain value (ε Fixed );

[0044] (2) The sample was gradually heated to 300°C at a heating rate of 5°C / min and kept at this temperature for 10 min to obtain the shape recovery strain value (ε Recover );

[0045] The temperature-stress-strain curve and shape fixity (R f ) and shape recovery rate (R r ) is calculated according to formulas (1) and (2), and the recovery rate is calculated by taking the time derivative of the strain:

[0046]

[0047]

[0048] Example 1

[0049] (1) 10.0115 g of 4,4'-diaminodiphenyl ether was dissolved in 144.2 ml of N-methylpyrrolidone, and 15.7405 g of biphenyltetracarboxylic dianhydride was added, and the mixture was reacted in an ice-water bath for 3 h; then, 4.25 ml of triethylamine was added, and the reaction was continued for 1.5 h to prepare a water-soluble polyamic acid solution with a solid content of 14.8%; the prepared water-soluble polyamic acid was precipitated with deionized water, and then washed and dried in a freeze dryer at -40°C for 72 h to obtain water-soluble polyamic acid dry silk;

[0050] (2) taking 0.075 g of carboxylated carbon nanotubes, adding them into 10 ml of ultrapure water, and dispersing them in a cell disruptor for 60 min to obtain a uniform dispersion of carboxylated carbon nanotubes;

[0051] (3) 0.9 g of the polyamic acid dry silk prepared in step (1) was dissolved in the carboxylated carbon nanotube dispersion prepared in step (2), 0.45 g of triethylamine was added, and then the mixture was placed in a magnetic stirrer on a heated stirring table at 60° C. and stirred for 1 h to obtain a solid-liquid mixed composite ink similar to a viscous slurry (the composite ink had a solid content of 8.5%);

[0052] (4) The composite ink was loaded into a syringe with a 0.35 mm needle. The shape path of the grid structure was imported into the 3D printer through the IGT drawing software. The air compressor provided power and the printing speed was set to 4 mms -1 , the printing air pressure was set to 0.17 MPa, the composite ink was squeezed out of the needle, and after printing, a composite ink with a grid structure was obtained, which was recorded as PCCI-1;

[0053] (5) The composite ink formed in step (4) was placed in a low-temperature constant temperature reaction bath at -80°C for 0.5 h for freezing, and then placed in a freeze dryer at -40°C for drying for 72 h. The obtained composite aerogel was thermally imidized at 300°C for 2 h to obtain a carboxylated carbon nanotube-reinforced polyimide aerogel with a three-dimensional grid structure, which was recorded as PCCA-1.

[0054] Example 2

[0055] The only difference from Example 1 is that the mass of the carboxylated carbon nanotubes in step (2) is adjusted to 0.15 g; the other conditions and parameters are the same as those in Example 1; wherein the composite ink with a three-dimensional grid structure obtained by 3D printing (the solid content of the composite ink is 9.1%) is recorded as PCCI-2; the obtained carboxylated carbon nanotube-reinforced polyimide aerogel with a grid structure is recorded as PCCA-2.

[0056] Example 3

[0057] The only difference from Example 1 is that the mass of the carboxylated carbon nanotubes in step (2) is adjusted to 0.225 g, and the other conditions and parameters are the same as those in Example 1; wherein the composite ink with a three-dimensional grid structure obtained by 3D printing (the solid content of the composite ink is 9.7%) is recorded as PCCI-3; the obtained carboxylated carbon nanotube-reinforced polyimide aerogel with a three-dimensional grid structure is recorded as PCCA-3.

[0058] Example 4

[0059] The only difference from Example 1 is that the mass of the carboxylated carbon nanotubes in step (2) is adjusted to 0.3 g, and the other conditions and parameters are the same as those in Example 1; the composite ink with a three-dimensional grid structure obtained by 3D printing (the solid content of the composite ink is 10.3%) is recorded as PCCI-4; the obtained carboxylated carbon nanotube-reinforced polyimide aerogel with a three-dimensional grid structure is recorded as PCCA-4.

[0060] Comparative Example 1

[0061] The only difference from Example 1 is that the mass of the carboxylated carbon nanotubes in step (2) is adjusted to 0 g, and the other conditions and parameters are the same as those in Example 1; the composite ink with a three-dimensional grid structure obtained by 3D printing (the solid content of the composite ink is 7.9%) is recorded as PAA ink; the polyimide aerogel prepared by cryo-assisted 3D printing is recorded as PIA.

[0062] Comparative Example 2

[0063] The only difference from Example 2 is that the carboxylated carbon nanotubes in step (2) are replaced by polyimide staple fibers in equal amounts, and other conditions and parameters are the same as those in Example 2; the composite ink having a three-dimensional grid structure obtained by 3D printing is denoted as PIFI; and the obtained polyimide aerogel is denoted as PIFA.

[0064] Comparative Example 3

[0065] The only difference from Example 2 is that the mass of the polyamic acid dry filaments in step (3) is adjusted to 2 g to form a composite ink (the solid content of the ink is 16.3%). Due to the high viscosity of the composite ink, 3D printing cannot be performed.

[0066] Comparative Example 4

[0067] The only difference from Example 2 is that the composite ink prepared in step (3) is directly poured into a mold, placed in a low-temperature constant temperature reaction bath at -80°C for 0.5 h for freezing, and then placed in a freeze dryer at -40°C for drying for 72 h. The obtained composite aerogel is thermally imidized at 300°C for 2 h.

[0068] Performance measurement

[0069] 1. Structural characterization of carboxylated carbon nanotube-reinforced polyimide aerogel

[0070] Figure 1 The composite ink in Example 2 was 3D printed to form a carboxylated carbon nanotube-reinforced polyimide aerogel butterfly pattern with a complex structure, indicating that the composite ink has good formability.

[0071] Figure 2 This is a SEM electron microscope image of the grid-structured carboxylated carbon nanotube-reinforced polyimide aerogel prepared in Example 2. Figure 2 As shown in a, the polyimide aerogel presents a regular four-square grid shape. Figure 2 b It can be seen that the interior of the polyimide aerogel presents a network porous structure, which is due to the pore structure left after the ice crystals sublimate during the freeze-drying process.

[0072] 2. Performance determination of carboxylated carbon nanotube-reinforced polyimide aerogel

[0073] The shape memory properties of the polyimide aerogels prepared in Examples 1 to 4 and Comparative Examples 1 and 2 were measured. The results are as follows: Figures 3 to 6 As shown in Table 1:

[0074]

[0075]

[0076] Table 1 Combination Figure 3 and Figure 4 It can be seen that, compared with Comparative Example 1, when preparing polyimide aerogels with shape memory properties, the shape fixation rate and shape recovery rate of the aerogels are not greatly affected by the amount of carboxylated carbon nanotubes used in Examples 1-4; however, the recovery rate of the polyimide aerogel is closely related to the content of the carboxylated carbon nanotubes, and the excessive or insufficient content of the carboxylated carbon nanotubes directly affects the recovery rate of the polyimide aerogel; when the content of the carboxylated carbon nanotubes is 15 mg / ml, the polyimide aerogel has the best shape memory property, with a shape fixation rate of 94.2%, a shape recovery rate of 96.6%, and a recovery rate of 4.8 min -1 .

[0077] Table 1 Combination Figure 5 and 6 The data show that the polyimide aerogel with added carboxylated carbon nanotubes has better shape memory properties than the polyimide aerogel with added polyimide staple fibers. Its shape fixation rate and shape recovery rate are higher than those of Comparative Example 2, especially the recovery rate. The recovery rate of the polyimide aerogel with carboxylated carbon nanotubes in Example 2 is 299.47% higher than that of Comparative Example 2.

[0078] Figure 7 (a) is the composite ink prepared in Comparative Example 3, and (b) is the composite ink prepared in Example 1; it can be seen that when the amount of polyamic acid in the ink increases, the solid content of the composite ink increases, and its viscosity increases accordingly, which in turn makes 3D printing impossible.

[0079] Figure 8 The figure shows the rheological properties of five different ink components prepared in Examples 1 to 4 and Comparative Example 1. It can be seen from the figure that the five different ink components still do not have a gel point under high shear strain and need to be assisted by freezing. At the same time, under high shear rate, the inks all show "shear thinning" characteristics, which meets the requirements of ink direct writing technology for ink viscosity.

[0080] Fig. 9 The polyimide aerogel prepared in Comparative Example 4 is Fig. 9 It can be seen that due to the high solid content of the ink, the aerogel formed by the mold is too hard to undergo a large degree of deformation, and thus the shape memory performance cannot be measured.

Claims

1. A method for improving the recovery rate of shape memory polyimide composite aerogel, characterized in that: The method comprises the following steps: (1) Add carboxylated carbon nanotubes into water and disperse them uniformly to form a carboxylated carbon nanotube dispersion; then add polyamic acid dry filaments and triethylamine to the carboxylated carbon nanotube dispersion, heat and stir to disperse them uniformly, and obtain a composite ink; the mass ratio of the carboxylated carbon nanotubes, polyamic acid and triethylamine is 1.5:9:4.5; the preparation of the polyamic acid dry filaments includes the following steps: firstly dissolving the polymerization monomer diamine in a polar solvent, then adding the dibasic anhydride monomer, and after the polymerization reaction in an ice water bath for 3-6 hours, adding the auxiliary solvent triethylamine, and continuing the reaction for 2-5 hours to obtain a polyamic acid solution; placing the obtained polyamic acid solution at a height of 0.5 m to 1 m, and slowly flowing it into ultrapure ice water, the polyamic acid settles and precipitates to obtain filamentous polyamic acid, and then freeze-drying the filamentous polyamic acid to obtain polyamic acid dry filaments; (2) The composite ink prepared in step (1) is loaded into a 3D printer for 3D printing and freeze-molding; the molded material is then placed in a freeze dryer for freeze drying and thermal imidization treatment to obtain a 4D printable shape memory polyimide composite aerogel having a three-dimensional grid structure.

2. The method according to claim 1, characterized in that The polymerizable monomer diamine includes 4,4'-diaminodiphenyl ether or p-phenylenediamine; the dianhydride monomer includes one or more of pyromellitic dianhydride, diphenyl ether tetracarboxylic dianhydride, 4,4'-biphenyl ether dianhydride, 3,3',4,4'-dibenzophenone tetracarboxylic dianhydride or biphenyl tetracarboxylic dianhydride.

3. The method according to claim 1, characterized in that The polar solvent includes one or more of N, N-dimethylacetamide, N-methylpyrrolidone or dimethylformamide.

4. The method according to claim 1, characterized in that The freeze molding in step (2) is carried out in a low-temperature constant-temperature reaction bath, the low temperature is -5°C~0°C; the temperature of the freeze dryer is -20°C~-50°C, and the time is 72 h~96 h.

5. The method according to claim 1, characterized in that The temperature of the thermal imidization in step (2) is 200-350° C. and the time is 1-3 h.

6. A 4D printable shape memory polyimide composite aerogel material prepared by the method described in any one of claims 1 to 5.

7. Application of the 4D printable shape memory polyimide composite aerogel material according to claim 6 in the preparation of automobiles, intelligent robots, aerospace vehicles, and intelligent wearable devices.

Citation Information

Patent Citations

  • 3D-printed fiber reinforced polyimide aerogel and preparation method thereof

    CN111138710A

  • Photo-thermal response three-dimensional shape memory polyimide, preparation method and application thereof

    CN111303425A